DAMPAK PEMBANGUNAN PARIWISATA AYU REZEKI PARK TERHADAP PERTUMBUHAN SOSIAL EKONOMI PADA MASYARAKAT SEKITAR - Abdurrohman, Abdurrohman (Universitas Jabal Ghafur, 2025)
Tourism is an activity that plays an important role in the economy as a source of state income. Tourism can be developed as a source of income, both as regional income in general and as income for the surrounding community in particular. Various parties such as the government, the private sector and the community who are directly involved by utilizing tourist attractions as business opportunities will be able to feel the positive impact of the tourism sector. In the research to be conducted, this study uses a qualitative approach with a descriptive research method. The qualitative approach is used by understanding the phenomena, behaviors, perceptions, and actions experienced by the research subjects, which must be understood descriptively. The descriptive method is a collection of sentences that express problems, conditions or events by collecting complete and clear data and information so that they can solve existing problems. The existence of Ayu Rezeki Park tourism has an impact on the economy of the surrounding community, namely the creation of business opportunities for the community, contributing to the local economy or income obtained by business actors, contributing to the Regional Original Income every year, and having an impact on the development of better infrastructure. The more active role of the relevant Agency to help promote tourist attractions so that they can be reached by tourists from outside the region. Cooperation is needed with related parties in order to develop this tourism better in the future, especially in terms of capital.